Clash of the Titans or Friendly Bedfellows? Freedom of Religion or Belief and Women’s Rights in India - Uma, Saumya (The review of faith & international affairs, 2022)
This article uses a case study of India to examine the contested relationship between two sets of human rights—freedom of religion or belief on the one hand, and women’s rights to life, dignity, equality, non-discrimination, sexual autonomy, and bodily integrity on the other. Through a critical analysis of the practice of female genital mutilation within the Bohra Muslim community, which is currently the subject of a constitutional challenge in the Supreme Court of India, this article illustrates how the contestations between the two sets of rights can be more effectively understood and addressed using the international human rights framework.